2022
DOI: 10.1159/000522424
|View full text |Cite
|
Sign up to set email alerts
|

Objective Response by mRECIST to Initial Lenvatinib Therapy Is an Independent Factor Contributing to Deep Response in Hepatocellular Carcinoma Treated with Lenvatinib-Transcatheter Arterial Chemoembolization Sequential Therapy

Abstract: Objective: There is limited information regarding the benefits of Lenvatinib-transcatheter arterial chemoembolization (LEN-TACE) sequential therapy for unresectable hepatocellular carcinoma (u-HCC). We compared the efficacy and safety of LEN-TACE sequential therapy to LEN monotherapy and investigated the factors contributing to the LEN-TACE sequential therapy deep response. Methods: We enrolled a multi-center cohort of 247 patients with u-HCC treated with LEN between 2018 and 2020. Propensity score matching id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…These reports differed from our study in the background of the HCC BCLC stage or the comparison of the treatment method (drug, TACE, etc.). Kuroda et al reported that LEN-TACE sequential therapy might provide more clinical benefits than LEN monotherapy in patients with unresectable HCC, including BCLC-C [ 18 ]. TACE was performed after assessing the therapeutic effect at 8 weeks after LEN treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These reports differed from our study in the background of the HCC BCLC stage or the comparison of the treatment method (drug, TACE, etc.). Kuroda et al reported that LEN-TACE sequential therapy might provide more clinical benefits than LEN monotherapy in patients with unresectable HCC, including BCLC-C [ 18 ]. TACE was performed after assessing the therapeutic effect at 8 weeks after LEN treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Responses was be assessed by the same imaging technology used at baseline, per modified Response Evaluation Criteria in Solid Tumors criteria, by two radiologists (reader 1, S.L., and reader 2, C.A., with 10 years of experience in abdominal imaging). 22 Early response (ER) was defined as OR occurring within 2 months of HAIC treatment. For those that were defined as having progressive disease, we administered the recommended lenvatinib (Eisai Co., Ltd, Tokyo, Japan) based on previous reports that it effectively improves prognosis.…”
Section: Methodsmentioning
confidence: 99%
“…The responses to HAIC were divided into OR including complete response and partial response, as well as non‐OR including stable disease and progressive disease. Responses was be assessed by the same imaging technology used at baseline, per modified Response Evaluation Criteria in Solid Tumors criteria, by two radiologists (reader 1, S.L., and reader 2, C.A., with 10 years of experience in abdominal imaging) 22 . Early response (ER) was defined as OR occurring within 2 months of HAIC treatment.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 573 articles were retrieved, and 244 repeated articles were excluded by title, year of publication, and author information. Then after reading abstracts and full-text screening, 311 articles that did not meet the criteria were excluded and finally included 18 studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (Fig. 1).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Seven studies [9,10,[13][14][15][16]18] provided 6-month, 12-month, and 18-month PFS rate data, of which 3 studies [9,14,18] were TACE plus lenvatinib versus TACE alone, and the other 4 studies [10,13,15,16] were TACE plus lenvatinib versus lenvatinib alone.…”
Section: Pfs Ratementioning
confidence: 99%